EFFECTIVENESS OF APPLYING MODERN METHODS IN FOREIGN LANGUAGE TEACHING - Mukhamedova, Odina Makhamadaliyevna (Innovative Development in Educational Activities, 2023)
In this article, the demand for learning a foreign language is also increasing day by day, the science of foreign languages is divided into four aspects (reading, reading, listening comprehension and speaking), each of which has its own concept and skills transfer, educational technologies, effective use of modern information technologies in this educational process and other similar topics will be discussed. It also aims to improve the quality and effectiveness of education through the introduction of modern innovative technologies in the educational process.